The role of prenatal cardiology in preventing fetal cardiac disease - Jičínská, Hana (2015)
Prenatal diagnoses of congenital heart defects (CHD), with subsequent early postnatal treatment and prenatal detection of severe heart rhythm disorders with adequate prenatal treatment, can prevent development of heart failure and positively impact the patient’s outcome. Detection of CHD in the first trimester of pregnancy also leads to early diagnosis of severe comorbidities in the fetus allowing the parents to consider continuation or early termination of the pregnancy. This paper examines CHD diagnosed in the first and second trimesters of pregnancy, the impact of first trimester screening on the spectrum of CHD and outcome of fetuses in second trimester and also the effect of treatment in fetuses with congenital complete heart block.